Huperzinea: Pharmacological and Therapeutic Potential - Upadhyay, Shagun Dubey; Ahmad, Yusra; Kumar Sharma, Rajesh; Kohli, Seema (Asian Journal of Biological and Life Sciences)
Introduction: Huperzine A (HupA) is derived from a club moss (Huperzia serrata). It is a potent and reversible inhibitor of acetyl cholinesterase (AChE). Chemically, it is a sesquiterpene alkaloid. It has been used for the treatment of swelling, fever and blood disorders for centuries in China. Methodology: The literature available on Huperzine was thoroughly studied. It has shown much beneficial effect since ages. It is a established Nootropic agent and widely used in the treatment of Alzheimer’s disease. The plant has shown promising results in vivo and in vitro studies. Results and Conclusion: The present review highlights the pharmacological potential of Huperzine with its pharmacokinetic and pharmacokinetic studies and it’s rational for future prospective.
Keywords: Huperzine; Pharmacology; Neuroprotective agent; Pharmacokinetics.